The Effect of Emotional Intelligence, Independence, and Leadership Style on Auditor Performance - Yoga Triatama; Panji Putranto (IAEI, 2023)
An auditor in carrying out an audit of financial statements does not solely work for the benefit of his client, but also for the benefit of other parties who have an interest in the audited financial statements. Therefore, in providing an opinion on the fairness of the financial statements being examined, public accountants must have high emotional intelligence, also be independent, and have a leadership style in order to influence the performance of an auditor. The sample used in the study was 30 respondents using a quantitative descriptive approach. Determination of sample size using non-random sampling technique because the population to be studied specifically. The data collection method uses a survey method, with the research instrument being a questionnaire. This study uses SPSS (Statistical Product and Service Solution) 25.0 for Windows, to measure the influence between the independent variable and the dependent variable and test the proposed hypothesis. This analysis is used to accept or reject the hypothesis. The results of this study state that the variables of emotional intelligence, and independence have no influence on auditor performance. Meanwhile, the leadership style variable has an influence on auditor performance.